Lecture Notes in Earthquake Engineering - Mohd Irwan, Adiyanto (Penerbit UMPSA, 2025)
This book is intended for a broad range of stakeholders in the field of civil engineering, including students, lecturers, researchers, consultants, contractors, and developers who seek to enhance their understanding of earthquake engineering from both theoretical and practical perspectives. The content is organized into five chapters, each systematically structured to develop foundational knowledge and applied insight. Chapter 1 provides an overview of earthquake disasters, encompassing the origins of seismic activity, fault mechanisms, and the associated effects of earthquakes. Chapter 2 examines ground motion records derived from real seismic events and introduces the concept of the response spectrum. Chapter 3 addresses the structural damage inflicted by earthquakes, with particular emphasis on topics such as building vibration, fundamental period, performance levels, and base shear force. Chapter 4 presents the principles of seismic design, including detailed guidance on the design of reinforced concrete structures in accordance with Eurocode 8 and Malaysia National Annex. Chapter 5 discusses seismic retrofitting techniques and contemporary technologies aimed at enhancing the seismic resilience of buildings. To make the content engaging and easy to follow, the book is primarily presented in the form of bullet points, mind maps, and flowcharts. In addition, a series of tutorials with relevant exercises are also included to reinforce learning.